Management innovations and social performance: What can we learn from looking at the adoption of liberation management practices? - Mattelin-Pierrard, Caroline; Dubey, Anne-Sophie; Battistelli, Matthieu (Management international / International Management / Gestiòn Internacional, 2023)
The effects of management innovations on performance are understudied, especially with respect to social performance. Our study contributes to this debate by examining the potential benefits of adopting liberation management, a typical management innovation when it comes to addressing a social performance gap. If employee empowerment is regarded as a lever of social performance in liberated companies, the extant literature does not reach a consensus on these alleged positive effects either. Our quantitative method – a quasi-experiment comparing two units (one liberated and another non-liberated) of a French industrial company – allows us to conclude that three liberation practices can in fact have a positive effect on social performance: participative decision-making, personalised support, and right to make mistakes.